Capsule Endoscopy for Ileitis with Potential Involvement of Other Sections of the Small Bowel - Hyun Seok Lee; Yun Jeong Lim (Gastroenterology Research and Practice)
Ileitis is defined as inflammation of the ileum. This condition includes ulcers, aphthous ulcers, erosions, and nodular or erythematous mucosa. Various etiologies are associated with ileitis. Crohn’s disease, ulcerative colitis, medications such as nonsteroidal anti-inflammatory drugs, infectious conditions, neoplasms, infiltrative disorders, vasculitides, spondyloarthritis, endometriosis, and radiation therapy-related conditions involve the ileum. However, the differential diagnosis of terminal ileitis can be difficult in many cases. Video capsule endoscopy (VCE) has become a useful tool for the diagnosis of a variety of small bowel lesions. This review describes each of the various conditions associated with ileitis and the diagnostic value of VCE for ileitis, which may help identify and evaluate these conditions in clinical practice. Based on the information provided by VCE, a definitive diagnosis could be made using the patients’ medical history, clinical course, laboratory and ileocolonoscopic findings, radiologic imaging findings, and histologic findings.